EFFICIENCY OF APPLICATION OF TECHNOLOGICAL METHODS OF REHABILITATION OF PATIENTS WITH CHILDREN'S CEREBRAL PARALYSIS (Archive of Conferences, 2021)
For many years, in both domestic and foreign studies, various means of neurorehabilitation of children with cerebral palsy have been proposed, mainly based on the principle of ontogenetic aspects, that is, a sequence corresponding to the development of the child's movements from birth to the moment of acquiring the walking skill. The most difficult is the approach to the methods of correction of children with a spastic form, in particular diplegia, since the limitation of movement is associated with organic damage to the central nervous system (1, 3, 4, 7).